Comparative Transcriptome Analysis Reveals Molecular Basis Underlying Fast Growth of the Selectively Bred Pacific Oyster, Crassostrea gigas - Zhang, Fuqiang; Hu, Boyang; Fu, Huiru; Jiao, Zexin; Li, Qi; Liu, Shikai (Frontiers in Genetics, 2019)
Fast growth is one of the most desired traits for all food animals, which affects the profitability of animal production. The Pacific oyster, Crassostrea gigas, is an important aquaculture shellfish around the world with the largest annual production. Growth of the Pacific oyster has been greatly improved by artificial selection breeding, but molecular mechanisms underlying growth remains poorly understood, which limited the molecular integrative breeding of fast-growth with other superior traits. In this study, comparative transcriptome analyses between the fast-growing selectively bred Pacific oyster and unselected wild Pacific oysters were conducted by RNA-seq. A total of 1303 protein-coding genes differentially expressed between fast-growing oysters and wild controls were identified, of which 888 genes were expressed at higher levels in the fast-growing oysters. Functional analysis of the differentially expressed genes (DEGs) indicated that genes involved in microtubule motor activity, and biosynthesis of nucleotides and proteins are potentially important for growth in the oyster. Positive selection analysis of genes at the transcriptome level showed that a significant number of ribosomal protein genes had undergone positive selection during the artificial selection breeding process. This results also indicated the importance of protein biosynthesis and metabolism for the growth of oysters. The alternative splicing (AS) of genes were also compared between the two groups of oysters. A total of 3230 differential alternative splicing events (DAS) were identified, involved in 1818 genes. These DAS genes were associated with specific functional pathways related to growth, such as “long-term potentiation”, “salivary secretion” and “phosphatidylinositol signaling system”. The findings of this study will be valuable resources for future investigation to unravel molecular mechanisms underlying growth regulation in the oyster and other marine invertebrates, and provide solid support for breeding application to integrate fast-growth with other superior traits in the Pacific oyster.